Roles, models and development trends of hi-tech industrial development zones in China. (27th September 2004) - Lingji, Li; Ping, Hu; Lei, Zhang
This paper focuses on the development of hi-tech Industrial Development Zones in China. Following the historical review and simple comparison of Economic-Technological Development Area (ETDA) and Hi-tech Industrial Development Zone (HIDZ), it examines three management models of HIDZ: government-oriented, enterprise-oriented and comprehensive management models. Furthermore, the paper explores HIDZ roles on Chinese economic development. Finally, it summarily analyses the new four trends of HIDZ in China.